Use of Ophthalmological Diagnostic Methods to Assess the Severity of Glomerulonephritis - D. Z., Djalalova; S. A., Boboev (American Journal of Bioscience and Clinical Integrity, 2025)
The study established a significant correlation between the severity of ophthalmological disorders and renal function indicators, which allows using these methods for a comprehensive assessment of the severity of the disease.